The Authority of the Mobile Brigade Unit in Handling Chemical, Biological, and Radioactive Materials at the Bali Provincial Police Headquarters - Dwipayudha, I Dewa Kadek; Sihotang, Erikson; Suandika , I Nyoman (CV. Syntax Corporation Indonesia, 2025)
The authority of the Mobile Brigade (Brimob) in handling chemical, biological and radioactive materials for terrorism purposes is based on the duties and functions of Brimob based on the legal basis of Law Number 2 of 2002 concerning the Indonesian National Police, namely implementing and deploying the strength of the Indonesian National Police Mobile Brigade to overcome high-level public order disturbances, especially mass riots, organized crimes involving firearms, bombs, chemical, biological and radioactive materials together with other operational implementing elements of the police in order to realize legal order and public peace throughout the jurisdiction of the Republic of Indonesia and other tasks assigned to it. In its authority, the Indonesian National Police Mobile Brigade is together with other police functions to take action against perpetrators of high-level crimes, especially mass riots, organized crimes involving firearms, bombs, chemical, biological and radioactive materials in order to realize legal order and public peace. However, there are obstacles in handling chemical, biological and radioactive materials for terrorism purposes in the form of internal and external factors.